IMPLEMENTASI KEBIJAKAN PROGRAM REHABILITASI SOSIAL RUMAH TIDAK LAYAK HUNI (RS-RTLH) DI DESA SUKAMANAH KECAMATAN CIMANGGU KABUPATEN SUKABUMI - Dede Rizal Kurniawan (Jurnal Dialektika Politik, 2025)
Implementation of the Social Rehabilitation Policy for Uninhabitable Houses is a process of restoring the social functioning of the poor through efforts to improve the condition of uninhabitable houses, either partially or completely, which are carried out in mutual cooperation so as to create conditions for proper housing as a place to live. This study aims 1. To find out the communication built in the Implementation of the Policy for the Social Rehabilitation Program for Uninhabitable Houses (RS-RTLH) in Sukamanah Village, Cimanggu District, Sukabumi Regency 2. To find out the resources related to the Implementation of the Policy for the Social Rehabilitation Program for Uninhabitable Houses (RS - RTLH) in Sukamanah Village, Cimanggu District, Sukabumi Regency 3. To find out the attitude of the implementers of the Policy Implementation of the Social Rehabilitation Program for Uninhabitable Houses (RS-RTLH) in Sukamanah Village, Cimanggu District, Sukabumi Regency 4. To find out the Bureaucratic Structure related to the Implementation of the Social Rehabilitation Program Policy Uninhabitable House (RS-RTLH) in Sukamanah Village, Cimanggu District, Sukabumi Regency. This study uses Edward III's theory in Subarsono (2015:90-92) which includes four dimensions, namely: 1. Communication, 2. Resources, 3. Disposition and 4. Bureaucratic Structure. The approach used in this study is a qualitative approach using descriptive methods. Data collection techniques using observation techniques, interviews, documentation, and applying triangulation techniques. With the tools that are interview guides, observation guides, field notes, recordings, and cameras. Then analyze the data by reducing data, presenting data, and drawing conclusions. This research was conducted in Sukamanah Village, Cimanggu District, Sukabumi Regency. The number of informants in this study were six people, namely the Head of Sukamanah Village, Secretary, Head of Hamlet, LPM, and two Beneficiary Families (KPM). with informant settings used are purposive sampling and snowball sampling. Based on the results of the study, the implementation of the social rehabilitation policy for uninhabitable houses in Sukamanah Village, Cimanggu District, Sukabumi Regency is not yet optimal, but it will be optimal if the factors are optimally increased so that with this policy it can create livable houses in Sukamanah Village.